2019
DOI: 10.1093/aobpla/plz002
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a relict distribution on genetic structure and variation in the Mediterranean tree,Platanus orientalis

Abstract: The distribution of plant species around the Mediterranean basin is a product of the influence of both geographical barriers and of climatic changes experienced during the Tertiary, with the transition from a warm to cool periods. Several species, once largely distributed across the Northern Hemisphere, retracted to refugial areas in southern Europe where they are described as Tertiary relicts. Platanus orientalis is a typical representative of Tertiary flora in southwest Eurasia; its distribution spreads from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 73 publications
1
20
2
Order By: Relevance
“…D.A. Webb ( N A = 17, Delplancke et al, ), or Phoenix dactylifera L. ( N A = 13, Zehdi‐Azouzi et al, ); but higher than in the Tertiary relict Platanus orientalis L. ( N A = 1.9, Rinaldi et al, ). La Malfa et al () reported a very similar N A value of 3.1 for nine SSR markers screened in carob cultivars from Italy, Malta and Spain.…”
Section: Discussionmentioning
confidence: 99%
“…D.A. Webb ( N A = 17, Delplancke et al, ), or Phoenix dactylifera L. ( N A = 13, Zehdi‐Azouzi et al, ); but higher than in the Tertiary relict Platanus orientalis L. ( N A = 1.9, Rinaldi et al, ). La Malfa et al () reported a very similar N A value of 3.1 for nine SSR markers screened in carob cultivars from Italy, Malta and Spain.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases it was considered as acceptable to take a minimum of 10 to 30 individuals. For some Pinus sylvestris L. populations in the Baltic area, the number of 20-25 individuals was found to be large enough to detect all the alleles (Danusevičius et al 2016) whereas other studies have even considered significantly lower numbers (Kitamura et al 2017, Rinaldi et al 2019. In contrast, in Kalinowski (2005) it was shown particularly clearly that when F ST is less than 0.01 it can be useful to sample up to 100 individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, we suggest that climatic changes in the recent past impacted forest distribution, leading to fragmentation of the forest in which Mexican Magnolia presently occur [23], and thus explaining the geographic distribution of the genetic variation. The in uence of the past glacial cycles was also observed in the Japanese Magnolia kobus [59] and the relict species Platanus orientalis, whose distribution is strongly in uenced by humidity and water availability, similar to magnolias [60].…”
Section: Discussionmentioning
confidence: 71%